Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1086/591484
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Survey of CO and H2in Diffuse Molecular Clouds: The Reflection of Two Photochemistry Regimes in Abundance Relationships

Abstract: We carried out a comprehensive far-UV survey of 12 CO and H 2 column densities along diffuse molecular Galactic sight lines. This sample includes new measurements of CO from HST spectra along 62 sight lines and new measurements of H 2 from FUSE data along 58 sight lines. In addition, high-resolution optical data were obtained at the McDonald and European Southern Observatories, yielding new abundances for CH, CH + , and CN along 42 sight lines to aid in interpreting the CO results. These new sight lines were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
391
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(439 citation statements)
references
References 152 publications
41
391
5
Order By: Relevance
“…In comparison with analogous studies, our estimates are different compared to the ratio of ∼2 × 10 −4 found for ∼50 K gas in Lacy et al (1994) but fall within the limits of log(CO/H 2 ) between -7.58 and -4.68 as measured by Sheffer et al (2008) for diffuse gas.…”
Section: Relation Between Co and Hcontrasting
confidence: 94%
“…In comparison with analogous studies, our estimates are different compared to the ratio of ∼2 × 10 −4 found for ∼50 K gas in Lacy et al (1994) but fall within the limits of log(CO/H 2 ) between -7.58 and -4.68 as measured by Sheffer et al (2008) for diffuse gas.…”
Section: Relation Between Co and Hcontrasting
confidence: 94%
“…In Fig. C.3 we show our model results for N(CH) versus N(H 2 ) together with the observational data (Rachford et al 2002;Magnani et al 2005Magnani et al , 2006Sheffer et al 2008;Qin et al 2010;Gerin et al 2010;Suutarinen et al 2011).…”
Section: D2 Column Densitymentioning
confidence: 67%
“…The column densities in our model are consistent with values for TMC-1 given by Suutarinen et al (2011) as well as with diffuse cloud observations presented by Gerin et al (2010) which give N(CH) ≈ 1−26 × 10 13 cm −2 for total H 2 columns between 10 21 −10 22 cm −2 . Sheffer et al (2008) present column densities along 42 diffuse molecular Galactic sight lines. They find total columns between 10 12 and 10 14 cm −2 and a very strong correlation between column densities of CH and H 2 .…”
Section: D2 Column Densitymentioning
confidence: 99%
“…For the diffuse low column density molecular clouds (no or very little CO) in the solar neighborhood, the H 2 layer containing C + is observed to have thermal pressures of order a few × 10 3 K cm −3 (cf. Sheffer et al 2008;Goldsmith 2013). Densities and temperatures, and therefore thermal pressures, have been determined from observations of absorption lines in the optical and UV for nearby low column density clouds.…”
Section: Pressure In the Co-dark H 2 Gasmentioning
confidence: 99%
“…Densities and temperatures, and therefore thermal pressures, have been determined from observations of absorption lines in the optical and UV for nearby low column density clouds. For example, Sheffer et al (2008) analyzed UV absorption lines of H 2 in diffuse molecular clouds with N(H 2 ) column densities up to ∼10 21 cm −2 (or A V ∼ 1 mag.) and derived T kin ranging from 50 to 120 K, with an average of 76 K in the molecular portion of the cloud.…”
Section: Pressure In the Co-dark H 2 Gasmentioning
confidence: 99%